The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.3855/jidc.6241
|View full text |Cite
|
Sign up to set email alerts
|

Complex class 1 integrons harboring CTX-M-2-encoding genes in clinical Enterobacteriaceae from a hospital in Brazil

Abstract: Introduction: CTX-M enzymes are the most prevalent extended-spectrum beta-lactamases (ESBLs) in Brazil and around the world. The spread of CTX-M lies in their ability to be mobilized by insertion sequences and integrons. This study aimed to identify the mobile genetic structures associated with bla CTX-M genes from clinical Enterobacteriaceae strains. Methodology: Twenty-eight clinical non-clonal Enterobacteriaceae were screened by PCR for the presence of bla CTX-M genes and class 1 integrase (int1), and for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 26 publications
3
11
0
1
Order By: Relevance
“…This is in congruence with previous data from our center that showed CTX-M-15 to be the most common ESBL enzyme produced among E. coli and Klebsiella species [18]. High prevalence of the CTX-M gene has been described in various reports from different geographical regions including Europe [21], Asia [22], and the Americas [23]. Of interest is evidence suggesting that this enzyme is expressed in bacterial strains harbored by dogs, livestock, and birds [24, 25].…”
Section: Discussionsupporting
confidence: 91%
“…This is in congruence with previous data from our center that showed CTX-M-15 to be the most common ESBL enzyme produced among E. coli and Klebsiella species [18]. High prevalence of the CTX-M gene has been described in various reports from different geographical regions including Europe [21], Asia [22], and the Americas [23]. Of interest is evidence suggesting that this enzyme is expressed in bacterial strains harbored by dogs, livestock, and birds [24, 25].…”
Section: Discussionsupporting
confidence: 91%
“…A few variants seem to be geographically constrained: (i) bla SHV-106 , only described in Portuguese isolates of K. pneumoniae together with bla TEM-1 , and/or bla CTX- M -32 (Mendonça et al, 2009); (ii) bla SHV-55 , in Portugal (Mendonça et al, 2006; Machado et al, 2007) and recently in Brazil (Dropa et al, 2015); and (iii) bla SHV-57 , in E. coli isolates from Taiwan and China (Ma et al, 2005; Tian et al, 2012). A variant worth to mention is bla SHV-27 (Corkill et al, 2001), that has been detected on different plasmids in E. coli, K. pneumoniae and Enterobacter cloacae , associated with a vast array of antibiotic resistance genes ( bla DHA−1 , bla TEM-1 , bla TEM−1b , bla CMY-2 , bla IMP , bla CTX- M -14 , bla CTX- M -15 , bla SHV-12 , bla SHV-45 , bla OXA-1 , dfrA5, ereA2 ; Muratani et al, 2006; Abbassi et al, 2008; Kiratisin et al, 2008; Duval et al, 2009; Hammami et al, 2011).…”
Section: Origin and Diversity Of The Shv Familymentioning
confidence: 99%
“…These variants have been described worldwide (Brazil, Portugal, Algeria, USA, Tunisia, Netherlands, France, South Africa, Colombia, and China) and are mostly associated to plasmids (Table 1). Some of these variants are sporadically accompanied by other antibiotic resistance genes like in the case of: (i) bla SHV-45 encoded by an IncA/C plasmid together with bla CTX- M -2 and bla SHV-27 (Dropa et al, 2015); (ii) bla SHV-134 encoded by an IncFII plasmid accompanied by a second plasmid carrying bla VIM−1 (Sánchez-Romero et al, 2012); (iii) and bla SHV-105 , conferring reduced susceptibility to ceftazidime, ceftriaxone, and aztreonam together with bla SHV-1 , and bla SHV-5 (Jones et al, 2009). One of the oldest variants, bla SHV-6 , was only described in France in 1991 in a K. pneumoniae clinical case (Arlet et al, 1991).…”
Section: Origin and Diversity Of The Shv Familymentioning
confidence: 99%
“…The bla CTX-M-2 was identified with lower frequencies and only in E. coli , as previously reported (38, 45). However, other studies reported higher bla CTX-M-2 frequencies in Enterobacteriaceae, with results ranging between 52.3% and 89.3% (41, 42, 46). For the bla KPC-like we found a 6.4% frequency for Enterobacteriaceae and 33.3% for K. pneumoniae isolated from patients, in accordance with previous studies (38, 47-50).…”
Section: Discussionmentioning
confidence: 85%